ศักยภาพชุมชน และที่อยู่อาศัยของชุมชนล่ามช้าง ในการเป็นย่านนวัตกรรมสร้างสรรค์ ภายใต้แผนพัฒนาเมืองอัจฉริยะ - กัญชุดา เพ็ญไชยา (คณะสถาปัตยกรรมศาสตร์ จุฬาลงกรณ์มหาวิทยาลัย, 2022)
In 2019, the government announced regional urban development policies according to the National Strategic Plan for determining Chiang Mai to be developed as a smart city to drive economic growth and improve people s quality of life. There are a total of 26 communities in the old city of Chiang Mai that have been designated as creative innovation districts. The results of the assessment of the composition of the creative district revealed that the "Lam Chang" community has the most potential for further development into an innovation district. The objective of this study is to assess the potential of the community by studying the physical, economic, social situation, needs, and attitudes of residents in the community and housing development to be in line with the smart city development plan. This study has specific methods including collecting data from the survey data analysis through geographic information systems, in-depth interviews, and mapping for all two action group meetings which mainly focus on participatory research. The results showed that the "Lam Chang" community has a high potential for development under the policy because its’ history of being the oldest trading community. Within the community, there are suitable for being a residential and workplace also have a temples, markets, and schools as the centers of the community which make the people in the community have high cooperation. The resources within the community are managed through the organization, committees, and also have a community’s enterprises. The houses in the "Lam Chang" have been modified to serve as a business activities. Most of them are adapted to accommodate tourists. However, The results of the workshop found that Community must be developed to be consistent with the policy plan in a practical way based on the existing assets and develoe a guidelines to promote new forms of activities and income consistent with the physical development. Last, Networking among communities, organizations, governments, and institutions is necessary to promote a fundraising.